Scoping review of cochlear implantation in Susac’s syndrome - Philip L. Pérez (KeAi Communications Co., Ltd., 2021)
Objective: Scoping review of published literature to establish clinical characteristics and audiologic outcomes in patients diagnosed with Susac’s Syndrome(SS) who have undergone cochlear implantation (CI). Data sources: All published studies of CI in SS and contribution of two of our own patients who have not been reported previously. Methods: A comprehensive search of MEDLINE (via PubMed) was carried out in March 2020 using the following keywords and related entry terms: Susac’s Syndrome, Cochlear Implantation. Results: Our search identified a total of five case reports of CI in SS. With the addition of our two patients reported here, we analyzed characteristics and outcomes in seven patients. Mean age at implantation was 30 years old (range 19–46), with six women and one man implanted. Mean time from onset of hearing loss to implantation was 17 months (range three months to four years). Best reported postoperative speech understanding was reported via different metrics, with six of seven patients achieving open set speech scores of 90% or better, and one subject performing at 68%. Vestibular symptoms were present preoperatively in four of seven patients (57%), with vestibular testing reported in two patients, and showing vestibulopathy in one patient. No complications were reported following cochlear implantation. Conclusion: Cochlear implantation is a viable option for hearing rehabilitation in patients with SS, with levels of attainment of open set speech comparable to other populations of CI candidates.